Serrated Polyps and Their Alternative Pathway to the Colorectal Cancer: A Systematic Review. (7th April 2015) - Szylberg, Łukasz; Janiczek, Marlena; Popiel, Aneta; Marszałek, Andrzej
Abstract : Colorectal cancer (CRC) is the third most frequently diagnosed cancer in the world. For a long time, only one pathway of colorectal carcinogenesis was known. In recent years, a new "alternative" pathway through serrated adenoma was described. Recent meta-analysis estimated these cancers as about 10% to 30% of all CRCs. Serrated polyps are the second most popular groups of polyps (after conventional adenomas) found during colonoscopy. Serrated polyps of the colon are clinically and molecularly diverse changes that have common feature as crypt luminal morphology characterized by glandular serration. Evidence suggests that subtypes of serrated polyps, particularly TSA and SSA/P, can lead to adenocarcinoma through the serrated pathway. Moreover, the data indicate that the SSA/P are the precursors of colorectal carcinoma by MSI and may be subject to rapid progression to malignancy. An important step to reduce the incidence of CRC initiated by the serrated pathway is to improve the detection of serrated polyps and to ensure their complete removal during endoscopy. Understanding of the so-called serrated carcinogenesis pathway is an important step forward in expanding possibilities in the prevention of CRC.